Security Of Chinese Citizens in Pakistan: Implications, Operational Challenges and Remedial Measures (Journal of Social Sciences Review, 2025)
This paper describes and analyses the security arrangement of Chinese citizens currently employed In the Islamic Republic of Pakistan in the wake of the rising wave of terrorism in CPEC and non-CPEC-related projects. It studies the current security arrangement in place, organizations of state deployed at both Federal and Provincial levels and their inter-departmental coordination. It also studies the latest security SOPs of the Home Department at a place for Chinese citizen's security. It will then employ deductive reasoning out of that security arrangement that is responsible for the current shortcomings exhibited in recent terror attacks and will then give recommendations to employ corrective measures which can reduce the probability of such security breaches.
Keywords: Security; Chinese Citizens; Pakistan; Remedial Measure; CPEC